Embedded Isoreticular Zeolites: Concept and Beyond. Issue 63 (18th September 2017) - Cho, Jung; Choi, Hyun June; Guo, Peng; Shin, Jiho; Zou, Xiaodong; Hong, Suk Bong
Abstract: The structure solution, prediction, and targeted synthesis of a family of embedded isoreticular zeolites (EIZs) with expanding structural complexity, denoted the RHO family, were reported recently. Here, the naming and building rules of body‐centered cubic EIZs with the lta cage as the lattice point are presented. The rearrangement of a pair of pau and d8r cages between two lta cages and its repetitive insertion, combined with the strong reflections and fragment methods, allows the creation of three other new zeolite families, designated the HPO, RHO(b), and KFI families. Among them, the KFI family is found to be the only EIZ family, on the basis of the similarity of structure factor amplitudes and phases of strong reflections, that is, structural coding, within its family members. The structural credibility of this family is confirmed by both local interatomic distances and T−T−T angle analyses. The existence of tetragonal EIZ families is also demonstrated. The overall results provide useful insights into the prediction of unprecedented EIZ families. Abstract : Defining embedded isoreticular zeolites : The definition and concept of embedded isoreticular zeolites can uncover a whole series of related structures (see figure) with similar structural properties and provide insight into their rational synthesis.